Immunometabolic Dysfunction of Natural Killer Cells Mediated by the Hypoxia-CD73 Axis in Solid Tumors - Chambers, Andrea M.; Matosevic, Sandro (Frontiers in Molecular Biosciences, 2019)
NK cell infiltration into solid tumors is often low and is largely represented by the poorly-cytotoxic CD56bright subset. Numerous studies have demonstrated that CD73, overexpressed under conditions of hypoxia, is involved in variety of physiological processes, while its overexpression has been correlated with tumor invasiveness, metastasis and poorer patient survival in many cancers. Hypoxia itself favors aggressive glycolytic fueling of cancer cells, in turn driving reprogramming of NK cell metabolism. In addition, the hypoxia-driven activity of CD73 immunometabolically impairs NK cells in tumors, due to its catalytic role in the generation of the highly immunosuppressive metabolite adenosine. Adenosinergic signaling was shown to alter NK cell metabolic programs, leading to tumor-promoting environments characterized by NK cell dysfunction. Despite the demonstrated role of NK cell responses in the context of CD73 targeting, the engagement of NK cells in the setting of hypoxia/CD73 signaling has not been extensively studied or exploited. Here, we discuss available evidence on the role of hypoxic signaling on CD73-mediated activity, and how this relates to the immunometabolic responses of NK cells, with a particular focus on the therapeutic targeting of these pathways.